Assessment of Efficacy of Different Whitening Agents on Dental Enamel: An In Vitro Study - Bandar Hamdan Alsuwayt; Raid marhjaldhafeeri; Fadi Fahad Alshammari; Abdulrahman Murhij Aldhafeeri; Bandr Zaal Al Shammeri; Faisal Zaal. M Alshalaqi; Ahmad Aqeel Z Alshammari (International Journal of Medical Toxicology and Legal Medicine, 2024)
Tooth whitening has become a popular cosmetic dental procedure. Various whitening agents are available, including hydrogen peroxide, carbamide peroxide, and sodium perborate. However, the efficacy of these agents on dental enamel is not well established. Which whitening agent is most effective in whitening dental enamel without causing significant surface changes or tooth sensitivity? This study will provide a comprehensive evaluation of the efficacy and safety of different whitening agents on dental enamel and will contribute to the development of evidence-based guidelines for tooth whitening procedures.